2017
DOI: 10.1158/1078-0432.ccr-16-1871
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Detection of EGFRvIII in Glioblastoma via Perfusion Magnetic Resonance Imaging Signature Consistent with Deep Peritumoral Infiltration: The ϕ-Index

Abstract: PURPOSE The epidermal growth factor receptor variant III (EGFRvIII) mutation has been considered a driver mutation and therapeutic target in glioblastoma, the most common and aggressive brain cancer. Currently, detecting EGFRvIII requires postoperative tissue analyses, which are ex vivo and unable to capture the tumor’s spatial heterogeneity. Considering the increasing evidence of in vivo imaging signatures capturing molecular characteristics of cancer, this study aims to detect EGFRvIII in primary glioblastom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 48 publications
2
70
0
Order By: Relevance
“…17 Dynamic susceptibility contrast (DSC) MR imaging may be helpful in preoperative diagnosis 18 of malignant lesions. Imaging features extracted from standard and advanced preoperative MR sequences can predict survival, molecular subtype, and mutational status in glioblastoma, 19,20 potentially enhancing the set of imaging biomarkers available to clinicians.…”
Section: Initial Diagnosis and Surgical Managementmentioning
confidence: 99%
“…17 Dynamic susceptibility contrast (DSC) MR imaging may be helpful in preoperative diagnosis 18 of malignant lesions. Imaging features extracted from standard and advanced preoperative MR sequences can predict survival, molecular subtype, and mutational status in glioblastoma, 19,20 potentially enhancing the set of imaging biomarkers available to clinicians.…”
Section: Initial Diagnosis and Surgical Managementmentioning
confidence: 99%
“…5). Its accuracy (89.92%), specificity (92.53%), sensitivity (83.77%), as well as its independent sample repeatability (Intra-class Correlation Coefficient (ICC) = 0.825) and reproducibility (ICC = 0.775), supports its potential routine clinical use [6, 7, 10]. Such signatures contribute to personalized medicine, and can enable non-invasive patient selection for targeted therapy, stratification into clinical trials, and repeatable monitoring of mutations during the treatment course.…”
Section: Results and Applicationmentioning
confidence: 94%
“…Extensive literature over the past decade has shown that rich panels of quantitative imaging features can result in non-invasive imaging signatures with diagnostic, prognostic and predictive value for many types of cancer, such as lung [38, 39], neck [38] and brain [2, 610, 40–43]. Specifically, these features have shown evidence of imaging signatures relating to underlying molecular characteristics, treatment response, patient survival, with the potential of augmenting conventional prognostic and predictive assays.…”
Section: Results and Applicationmentioning
confidence: 99%
See 2 more Smart Citations